Medio-Lateral Hamstring Muscle Activity in Unilateral vs. Bilateral Strength Exercises in Female Team Handball Players – A Cross-Sectional Study - Brian Sørensen; Per Aagaard; Lasse Malchow-Møller; Mette Kreutzfeldt Zebis; Jesper Bencke (International Journal of Sports Physical Therapy)
# Background